Ocorrência de Dictyla monotropidia Stål (Hemiptera: Tingidae) em Cordia verbenacea Al. DC no Brasil - Rosa, Daniel D. [UNESP]; Basseto, Marco A. [UNESP]; Feliciano, Fernanda; Neves, Monica B.; Baldin, Edson L. L. [UNESP] (Springer Nature, 2008)
Recently, Dictyla monotropidia Stål was observed feeding on plants of black sage (Cordia verbenacea Al. DC). The colonies of this insect were observed on abaxial surface of leaves, with nymphs and adults sucking the phloem sieve, causing spot, yellow aspect and leaf fall. D. monotropidia was already related as pest in other Cordia species in countries of Central and South America. Although, this is the first report of this insect attacking plants of C. verbenacea in Brazil.
Occurrence of Dictyla monotropidia Stål (Hemiptera: Tingidae) on Cordia verbenacea Al. DC in Brazil
Keywords: Black sage; Lace bug; Medicinal plant